Klasifikasi Kematangan Buah Tin Menggunakan Convolutional Neural Network Berbasis Android - Maulana Aditya Yusman; Evanita Evanita; Aditya Akbar Riadi (Jurnal Teknik Informatika dan Sistem Informasi, 2023)
Fig is a fruit that comes from the Middle East. However, there are several figs that can be found in Indonesia, such as Green Jordan Fig. A lot of people like this fruit because of its sweet taste and has many benefits to be used as medicine. The classification of fig ripeness generally uses subjective human eye so that it can cause errors due to the insignificant characteristics of fig ripeness when ripe and inripe, when ripe it is light green, slightly yellowish, while when inripe the fruit is green. Therefore, the author got the idea to make an application for classification of fig ripeness via image based on Android using the Convolutional Neural Network algorithm. In this study, the results obtained accuracy of 94%.